Pendampingan Perencanaan Saluran Irigasi di Desa Sambirejo Kecamatan Wirosari Kabupaten Grobogan - Kukuh Wisnuaji Widiatmoko; Bagus Acung Billahi; Faizal Mahmud (Jurnal Pengabdian KOLABORATIF, 2025)
One way to utilize water resources is through the development of irrigation networks. Two common approaches to irrigation planning are the expansion method and the intensification method. Sambirejo Village is one of the areas with extensive land that can be used for rice cultivation. However, due to the large agricultural area, several paddy fields do not consistently receive a water supply from the existing irrigation network. Geographically, Sambirejo Village is located near both large and small rivers, which can be utilized as sources of irrigation water. The main issues faced by the local partners include a lack of understanding in planning irrigation channels to ensure optimal functionality. As a result, existing irrigation systems do not operate as intended, and the community has not yet been able to harness the full potential of the nearby water sources for irrigation purposes. To improve the availability of irrigation water in Sambirejo Village, the activity aimed to provide partners with knowledge on irrigation channel planning, as well as insights into watershed areas that can serve as water sources and the layout of rice fields to be irrigated. The implementation method involved providing explanations on how the irrigation system was designed to utilize gravity flow without pumps, and demonstrating the positive impacts of a properly functioning irrigation network. As a result of the activity, a priority area of approximately 1,200 meters was identified for irrigation channel planning. Technical planning documents were also prepared, including working drawings, channel dimensions, field measurement results, and a cost estimate (RAB), which can be used as a basis for proposing development programs funded by village budgets or related government agencies.